Mitochondrial dysfunction in the fetoplacental unit in gestational diabetes mellitus - Sobrevia, Luis; Valero, Paola; Grismaldo, Adriana; Villalobos-Labra, Roberto; Pardo, Fabián; Subiabre, Mario; Armstrong, Gael; Toledo, Fernando; Vega, Sofía [UNESP]; Cornejo, Marcelo; Fuentes, Gonzalo; Marín, Reinaldo (Elsevier, 2020)
Gestational diabetes mellitus (GDM) is a disease of pregnancy that is associated with D-glucose intolerance and foeto-placental vascular dysfunction. GMD causes mitochondrial dysfunction in the placental endothelium and trophoblast. Additionally, GDM is associated with reduced placental oxidative phosphorylation due to diminished activity of the mitochondrial F0F1-ATP synthase (complex V). This phenomenon may result from a higher generation of reactive superoxide anion and nitric oxide. Placental mitochondrial biogenesis and mitophagy work in concert to maintain cell homeostasis and are vital mechanisms securing the efficient generation of ATP, whose demand is higher in pregnancy, ensuring foetal growth and development. Additional factors disturbing placental ATP synthase activity in GDM include pre-gestational maternal obesity or overweight, intracellular pH, miRNAs, fatty acid oxidation, and foetal (and ‘placental’) sex. GDM is also associated with maternal and foetal hyperinsulinaemia, altered circulating levels of adiponectin and leptin, and the accumulation of extracellular adenosine. Here, we reviewed the potential interplay between these molecules or metabolic conditions on the mechanisms of mitochondrial dysfunction in the foeto-placental unit in GDM pregnancies.
Keywords: Adenosine; Endothelium; Gestational diabetes; Human; Insulin; Mitochondria; Placenta